Energy utilization by sheep and buffalo from a roughage ration at maintenance level of feeding - Murarilal, Murarilal; Khan, M Y; Haque, N (The Indian Journal of Animal Sciences, 2012)
Adult male Murrah buffaloes (4) weighing 350 kg, and 6 rams of 13 kg were fed on oat green and wheat straw in the same ratio for their maintenance. Energy distribution was determined in an open circuit respiration chamber. The dry matter intakes of 65.5 and 58.6 g/kg Wâ°Ë™â·âµÌ‡/day in buffalo and sheep, respectively. were significantly (P